On the intersection of two longest paths in k-connected graphs - Gutiérrez, Juan (Pontificia Universidad Católica del Perú, 2021)
Mostramos que cada par de caminos máximos en un grafo k-conexo con n vértices se intersecan uno al otro en por lo menos mín{n, (8k − n + 2)/5} vértices. También mostramos que en un grafo 4-conexo cada par de caminos máximos se interseca uno al otro en por lo menos cuatro vértices. Ello conﬁrma una conjetura de Hippchen en grafos k-conexos cuando k ≤ 4 o k ≥ (n − 2)/3.

We show that every pair of longest paths in a k-connected graph on n vertices intersect each other in at least min{n, (8k − n + 2)/5} vertices. We also show that, in a 4-connected graph, every pair of longest paths intersect each other in at least four vertices. This confirms a conjecture of Hippchen for k-connected graphs when k 4 or k (n − 2)/3.
Keywords: Grafo k-conexo; Camino máximo; https://purl.org/pe-repo/ocde/ford#1.01.00